2017
DOI: 10.1093/gbe/evx160
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Variation Patterns Uncover the Origin and Selection in Cultivated Ginseng (Panax ginseng Meyer)

Abstract: Chinese ginseng (Panax ginseng Meyer) is a medicinally important herb and plays crucial roles in traditional Chinese medicine. Pharmacological analyses identified diverse bioactive components from Chinese ginseng. However, basic biological attributes including domestication and selection of the ginseng plant remain under-investigated. Here, we presented a genome-wide view of the domestication and selection of cultivated ginseng based on the whole genome data. A total of 8,660 protein-coding genes were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…To analyze population structure, various methods such as STRUCTURE and principal coordinates analysis have been used for ginseng germplasm [19,20,58]. In this study, STRUCTURE and DAPC used to analyze the population structure of 1109 ginseng accessions appeared to provide complementary information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze population structure, various methods such as STRUCTURE and principal coordinates analysis have been used for ginseng germplasm [19,20,58]. In this study, STRUCTURE and DAPC used to analyze the population structure of 1109 ginseng accessions appeared to provide complementary information.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity of germplasm can be investigated using various techniques, including analysis of morphological and agricultural traits [13], isozymes [14], biochemical characteristics [15], and molecular markers [14][15][16]. In recent years, the development of various chemical and molecular techniques for differentiation among P. ginseng samples has received attention [10,[17][18][19][20]. Gepts has reported that DNA markers are the most reliable ones for distinguishing variations of alleles because these markers are not influenced by environmental or physiological factors [21].…”
mentioning
confidence: 99%
“…In the case of P. notoginseng , for example, increasing in specific leaf area and chlorophyll content are negatively correlated with the growth irradiance level (Chen et al, 2014 , 2016 ). Likewise, cytoplasmic proteins of P. ginseng encoded by both cytoplasmic and nuclear genomes are the targets of selection during local adaptation and domestication processes (Li et al, 2017 ). These attributes together suggest that cytoplasmic genes may have evolved non-neutrally in the Panax species.…”
Section: Discussionmentioning
confidence: 99%
“…All these Panax species are shade-demanding perennial herbs and inhabit the cool shaded habitats (Liu and Xiao, 1992 ; Chen et al, 2014 , 2016 ). In the case of the agro-economically important species P. ginseng , while cultivated ginseng harbored similar level of nucleotide diversity compared to the wild ginseng in the nuclear genome, obviously lower sequence polymorphisms were found in the chloroplast genome of cultivated ginseng (Li et al, 2015 , 2017 ). Specifically, cytoplasmic genomes as well as the cytoplasmic proteins encoded by the nuclear genome are the targets of selection in the cultivated ginseng during local adaptation and domestication processes (Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation